Treating Acute Leukemia During the COVID-19 Pandemic in an Environment With Limited Resources: A Multicenter Experience in Four Latin American Countries - Demichelis-Gómez, R (2021)
Purpose: The COVID-19 pandemic is a colossal challenge for global health; nonetheless, specific subgroups face considerably higher risks for infection and mortality. Among patients with malignant diseases, those with hematologic neoplasms are at a higher risk for poor outcomes. The objective of this study was to register treatment modifications associated with the COVID-19 pandemic and their short-term consequences in Latin America. Methods: Multicenter, prospective, observational, cohort study including patients older than 14 years from 14 centers in four countries (Mexico, Peru, Guatemala, and Panama) who had a confirmed diagnosis of acute leukemia, and who were undergoing active treatment since the first COVID-19 case in each country until the cutoff on July 15, 2020. Results: We recruited 635 patients. Treatment modifications because of the COVID-19 pandemic were reported in 40.8% of cases. The main reason for such modifications was logistic issues (55.0%) and the most frequent modification was chemotherapy delay (42.0%). A total of 13.1% patients developed COVID-19 disease, with a mortality of 37.7%. Several factors were identified as independently associated with mortality, including a diagnosis of acute myeloid leukemia (odds ratio 2.38 [95% CI, 1.47 to 3.84]; P < .001), while the use of telemedicine was identified as a protective factor (odds ratio 0.36 [95% CI, 0.18 to 0.82]; P = .014). Conclusion: These results highlight the collateral damage of COVID-19 in oncology patients.